The chief European dramatists: Twenty-one plays from the drama of Greece, Rome, Spain, France, Italy, Germany, Denmark, and Norway, from 500 B.C. to 1879 A.D. - Matthews, Brander; Riverside Press (Cambridge, Mass.) (Houghton Mifflin company, 1916)
Twenty one plays from the drama of Greece, Rome, Spain, France, Italy, Germany, Denmark, and Norway from 500 B. C. to 1879 A.
Includes bibliographical references.
Agamemnon, by Æschylus, tr. by E. D. A. Morshead.--Œdipus the king, by Sophocles, tr. by Sir R. C. Jebb.--Medea, by Euripides, tr. by G. Murray.--The frogs, by Aristophanes, tr. by J. H. Frere.--The captives, by Plautus, tr. by E. H. Sudgen.--Phormio, by Terence, tr. by M. H. Morgan.--The star of Seville, by Lope de Vega, tr. by P. M. Hayden.--Life is a dream, by Calderon, tr. by D. F. MacCarthy.--The Cid, by Corneille, tr. by F. K. Cooper.--Tartuffe, by Moliére, tr. by C. H. Page.--Phædra, by Racine, tr. by R. B. Boswell.--The barber of Seville, by Beaumarchais, tr. by A. B. Myrick.--Hernani, by Victor Hugo, tr. by Mrs. N. Crosland.--The son-in-law of M. Poirier, by Augier and Sandeau, tr. by B. H. Clark.--The outer edge of society, by A. Dumas, fils, tr. by B. H. Clark.--The mistress of the inn. by Goldoni, tr. by M. Pierson.--Minna von Barnhelm, by Lessing, tr. by E. Bell.--Goetz von Berlichingen, by Goethe, tr. by Sir W. Scott.--William Tell, by Schiller, tr. by Sir T. Martin.--Rasmus Montanus, by Holberg, tr. by O. J. Campbell and F. Schenck.--A doll's house, by H. Ibsen, tr. by W. Archer.--Appendix: Notes on the authors. Notes on the plays. A reading list in European dramatists (p. [784]-786)
Twenty one plays from the drama of Greece, Rome, Spain, France, Italy, Germany, Denmark, and Norway from 500 B. C. to 1879 A.
Keywords: Drama; French drama (Comedy) / Translations into English.; Greek drama / Translations into English; Drama / Translations into English.; Translations / fast; Drama / fast